A-Z guide for sports research / Azlina Zid … [et al.] - Zid, Azlina; Samat, Hajar Azmidar; Shaari, Jamatul Shahidah; Kusrin, Jamiaton; Mohd Nor, Maizan; Muhammad Rafiai, Nurul Ain; Wahab, Siti Aishah
The guidance for the preparation of the Research Project sets the minimum standard requirements for the format and final form of the Bachelor in Sports Science (Hons.) and Bachelor in Sports Management (Hons.) report that must be met in order to gain the approval of the Faculty of Sports Science and Recreation Research Committee. This guide has been prepared to help undergraduate students prepare their research project to be accepted by the Faculty of Sports Science and Recreation. The guideline contained will benefit the students and supervisors from departments of Sports Science and Sports Management. A research project has to be written by the Faculty Research Project format with the citations and references referring to the 6th Edition of American Psychological Association (APA) styles. It is the supervisor's responsibility to make certain that the research submitted in partial fulfillment of an undergraduate degree at the faculty conforms to the regulations outlined in this guide. The content of the project report remains to be the responsibility of the student and the supervisor(s).The final approval for the content of the research project will be the supervisors and students' sole responsibility.